Location and interrelations of the roma quarter of Harman Mahala with the urban structure of the city of Plovdiv, Bulgaria - Nadezhda ILIEVA; Omar KOUWATLI; Krasimir ASENOV; Boris KAZAKOV (European Journal of Geography)
The main objective of this study is to analyse the location and the spatial interrelations of the Roma-populated Harman Mahala quarter of the city of Plovdiv, Bulgaria. Three types of boundaries of the ghettoized urban structure (GUS) have been distinguished – "solid", "blurry" and "symbolic". The solid boundaries are outlined taking into account the urban space inhabited by the Roma ethnic community, i.e. from a "static" point of view. In defining the “blurry” boundaries of the GUS, the specifics of the residents’ spatial behaviour were analyzed. Movement in space is closely linked to the following “functional spaces”: labour, education, recreation and leisure, sports, commerce, healthcare, transport and commuting, with their inherent material and technical facilities, organizational structure and interactions.Through those interactions, the so-called “functional space” is outlined. The third aspect taken into consideration is the outlining of the so-called "symbolic space" of the GUS, the boundaries of which are dependent on how the local Roma population perceives the urban space.